Flexible wireless magnetic closure sensor: A biocompatible device for real-time biomedical applications - Runxing Lin; Ziyu Huang; Yu Liu; Bingpu Zhou; Yinning Zhou (Sensors and Actuators Reports)
Traditional sensors face significant challenges in applications such as rehabilitation training and intraoperative monitoring. These challenges include limited operational flexibility due to wired connections, insufficient conformity of rigid designs to dynamically deforming regions, difficulty in observing and quantifying organ muscle movements, and poor performance in real-time monitoring of muscle coordination patterns. To address these limitations, this study developed a flexible wireless magnetic closure sensor (FWMCS) based on the principle of electromagnetic induction. Inspired by magnetic clasp in daily life, this sensor combines real-time monitoring, wireless operation, flexible adaptability, cost-effective manufacturing, and biocompatibility, enhancing its adaptability and reliability in complex dynamic environments, including rehabilitation training and intraoperative monitoring. Experimental results demonstrated that the FWMCS performed excellently in scenarios such as joint rehabilitation training and physiological displacement monitoring. It accurately captured dynamic motion signals and enabled efficient functional assessments, showing compatibility with various rehabilitation programs. Its lightweight, modular design and elimination of the need for professional technical requirements make it suitable for home rehabilitation.